Use of Healthcare Services Two Years before Diagnosis in Danish Sarcoma Patients, 2000–2013. (7th May 2019) - Rædkjær, Mathias; Maretty-Kongstad, Katja; Baad-Hansen, Thomas; Safwat, Akmal; Petersen, Michael M.; Keller, Johnny; Vedsted, Peter
Abstract : Background . Sarcoma is a rare type of cancer with nonspecific symptoms and uncertain aetiology. Thus, timely diagnosis of sarcomas is a clinical challenge. The aim of this study was to investigate the use of healthcare services 24 months preceding a sarcoma diagnosis compared to a matched cohort. Materials and Methods . The study was a retrospective, population-based, matched cohort registry-study. Patients with sarcoma in Denmark in 2000–2013 were identified in the Danish Sarcoma Registry ( n = 2167) and matched 1 : 10 on gender, age, and listed general practice. Using a binomial regression model, incidence rate ratios were calculated for face-to-face contacts in general practice, inpatient and outpatient visits, surgery, paraclinical examinations, and diagnostic imaging. Analyses were stratified for sarcoma subtypes, grade, stage, gender, and presence of comorbidity. Results . The sarcoma patients had significantly increased incidence rate ratios in use of healthcare services compared to the matched cohort a year before their diagnoses. An increase in consultation rates was seen 11 months before diagnosis for inpatient visits, 9 months before diagnosis in general practice and outpatient visits, 8 months before diagnosis for paraclinical examinations, and 4 and 3 months before diagnosis for diagnostic imaging and surgery, respectively. There were no clinical significant differences in length of increased consultation rates between sarcoma type, stage, and grade. Sarcoma patients with comorbidity had persistently higher consultation rates compared to patients without comorbidity. Conclusions . The use of healthcare services among sarcoma patients increased several months before diagnosis in all healthcare sectors. The results reveal a diagnostic time window and a potential to refer, diagnose, and treat sarcoma patients in a timelier manner.